2017
DOI: 10.1038/s41598-017-16364-8
|View full text |Cite
|
Sign up to set email alerts
|

Emergent wave phenomena in coupled elastic bars: from extreme attenuation to realization of elastodynamic switches

Abstract: Metamaterials with acoustic and elastic band gaps are of great interest to scientists and engineers. Here, we introduce a novel mechanism for emergence of multiple band gaps with extreme attenuation by coupling continuous one-dimensional elastic structures. We show that it is possible to develop extreme attenuation at several frequencies from coupling two homogenous bars of different elastodynamic properties even though each bar individually possesses no such gaps. Moreover, if each bar is a composite on its o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Perhaps the most prominent thrust in metamaterials research aims at controlling waves for potential applications such as lensing, cloaking and noise reduction (Milton et al, 2006, Chen et al, 2010, Parnell and Shearer, 2013, Bigoni et al, 2013, Colquitt et al, 2014, Cummer et al, 2016. This interest led to a renewed study of wave mechanics in optics (Markos andSoukoulis, 2008, Banerjee, 2011), acoustics Guenneau, 2012, Deymier, 2013), mechanical lattices (Phani, 2011, Raney et al, 2016, Phani and Hussein, 2017, Zelhofer and Kochmann, 2017, Ma et al, 2018 and elastodynamics (Brun et al, 2010, Shmuel and Band, 2016, Chen and Elbanna, 2017, Aghighi et al, 2019, Li and Reina, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most prominent thrust in metamaterials research aims at controlling waves for potential applications such as lensing, cloaking and noise reduction (Milton et al, 2006, Chen et al, 2010, Parnell and Shearer, 2013, Bigoni et al, 2013, Colquitt et al, 2014, Cummer et al, 2016. This interest led to a renewed study of wave mechanics in optics (Markos andSoukoulis, 2008, Banerjee, 2011), acoustics Guenneau, 2012, Deymier, 2013), mechanical lattices (Phani, 2011, Raney et al, 2016, Phani and Hussein, 2017, Zelhofer and Kochmann, 2017, Ma et al, 2018 and elastodynamics (Brun et al, 2010, Shmuel and Band, 2016, Chen and Elbanna, 2017, Aghighi et al, 2019, Li and Reina, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…This work also highlights the role of stiffness variation in material design particularly related to problems in fracture or adhesion. Heterogeneities in general, through patterning the bulk geometry, introducing voids, introducing patterned cuts, or adding soft or hard inclusion may result in materials with enhanced fracture toughness [36], wave propagation properties [37], negative Poisson's ratio [38], or improved adhesion [38,39], among other material properties. This opens new pathways in designing and fabricating metamaterials with optimized and enhanced material priorities.…”
Section: Accepted Manuscript N O T C O P Y E D I T E Dmentioning
confidence: 99%
“…More recently, Chen and Elbanna studied the coupling of a pair of bars in parallel and showed that tailoring the properties of the two elastic members may lead to extreme attenuation zones in the band structure of the system. The idea was then used to realize a mechanical switch that is used to modulate elastic waves [38].…”
Section: Introductionmentioning
confidence: 99%